INCREASING INTENSIVE STUDY BY USING COMBINATION MODEL OF THE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC), TEAM ASSISTED INDIVIDUALIZATION (TAI), AND NUMBERED HEAD TOGETHER (NHT) - Azizah, Azizah; Ramadi, Ramadi; Noviyanti, Noviyanti (Journal of K6, Education and Management, 2018)
The purpose of this study is to determine the activities of the teacher, student activities and student learning outcomes read intensive through the combination of learning models Cooperative Integrated Reading and Composition (CIRC), Team Assisted Individualization (TAI) and the Numbered Head Together (NHT). This research is using class behavior research which is done in 2 cycles. Research setting is in the SDN Pengambangan 9 East Banjarmasin school year 2016/2017 2nd semester in grade IV. The results showed that there is an increase in each cycle. It can be seen from the teacher's activity in the cycle that earned the score 33 with category "Good" and in cycle II that earned score 42 with the category "Very Good". The student's activity in the learning process in cycle I am classically 46% with the category of "Quite Active" and in cycle II is classically 75% with category ?Active?. Meanwhile, the student?s learning result classically in cycle I reaches 81% and it increases to 92% in cycle II.